2015
DOI: 10.4269/ajtmh.14-0378
|View full text |Cite
|
Sign up to set email alerts
|

Observed Practices and Perceived Advantages of Different Hand Cleansing Agents in Rural Bangladesh: Ash, Soil, and Soap

Abstract: Abstract. Bangladeshi communities have historically used ash and soil as handwashing agents. A structured observation study and qualitative interviews on the use of ash/soil and soap as handwashing agents were conducted in rural Bangladesh to help develop a handwashing promotion intervention. The observations were conducted among 1,000 randomly selected households from 36 districts. Fieldworkers observed people using ash/soil to wash their hand(s) on 13% of occasions after defecation and on 10% after cleaning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Multiple factors can affect handwashing with soap: contextual (having a shared courtyard and the associated inconvenience), psychosocial (perceived value of handwashing), and technological (ease of use, handwashing station wear and tear) . In a qualitative study in rural Bangladesh, key informants stated that they purchased bar soap primarily for bathing and laundry because soap was perceived to be an expensive items that could not be used for all purposes, including handwashing, and some informants did not keep soap at the handwashing place in order to conserve soap . The practice of keeping soap away from handwashing place may not be as common in urban settings, where latrines have a place to keep soap and water .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple factors can affect handwashing with soap: contextual (having a shared courtyard and the associated inconvenience), psychosocial (perceived value of handwashing), and technological (ease of use, handwashing station wear and tear) . In a qualitative study in rural Bangladesh, key informants stated that they purchased bar soap primarily for bathing and laundry because soap was perceived to be an expensive items that could not be used for all purposes, including handwashing, and some informants did not keep soap at the handwashing place in order to conserve soap . The practice of keeping soap away from handwashing place may not be as common in urban settings, where latrines have a place to keep soap and water .…”
Section: Discussionmentioning
confidence: 99%
“…Guided by the model and extensive formative research , the behaviour change intervention was designed to improve stable access to enabling technologies (handwashing stations and soapy water dispensers) placed conveniently in or around the home, increase handwashing skills of adults and children, build family and community support in maintaining the handwashing stations and replenishing supplies, influence community norms by modelling and supporting the behaviour in public, and provide periodic counselling and problem solving by trained community health workers. In Bangladesh, the cost of bar soap is perceived to be a barrier to frequent handwashing with soap ; a bar of soap costs 40 Taka (US $0.50) in a country where the minimum wage for a common occupation such as garment factory work is $67 per month . Soapy water is a mixture of powder detergent soap and water and is a microbiologically effective cleansing agent .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though half of the informants stated the need to wash hands with soap before preparation of some foods, such as salads and bhortas, they only recognized this as important when there was visible dirt on hands, as reported for handwashing in general in previous studies from Bangladesh 30,31 and elsewhere. 32,33 Both types of observation methods confirmed that community members did not wash hands with soap during food preparation.…”
Section: Occurred 1 Timementioning
confidence: 94%
“…Washing hands with water is common in the community from where the data for the current study was collected [24, 25]. While washing hands with soap has optimal health benefits, washing hands with water only is more beneficial than not washing hands at all [24].…”
Section: Introductionmentioning
confidence: 99%